Post-COVID Corporate Financial Reports: Adapting to New Challenges and Emerging Regulations - Tanjung, Akbar; Hidayat, Muhammad (Penelitian dan Pengembangan Ilmu, 2024)
In the post-COVID-19 context, corporate financial reporting practices are undergoing significant transformation to face new global economic challenges. This research aims to understand the adaptation of financial reporting practices in facing post-pandemic conditions, with a focus on new strategies implemented by companies to maintain transparency and relevance of financial information. Through a systematic review of academic literature, research results show that many companies are adopting new technologies, improving financial risk analysis, and strengthening corporate governance to respond to regulatory changes and dynamically changing market needs.